Adipose-Derived Molecules–Untouched Horizons in Alzheimer’s Disease Biology - Pichiah, P. B. Tirupathi; Sankarganesh, Devaraj; Arunachalam, Sankarganesh; Achiraman, Shanmugam (Frontiers in Aging Neuroscience, 2020)
Global incidence of Alzheimer’s disease (AD) is on rise paralleling with the obesity and metabolic disease epidemic. Obesity is co-morbid with increase of mass of adipose tissue, which secrete numerous factors that are biologically important. Obesity and its associated conditions are perhaps involved in the causative pathway of AD. Immunologically important cytokines such as IL-1β, IL-10, and IL-18, which are released by adipose tissues are also found associated with AD. All these cytokines play key roles in regulating autophagy. Besides, expression of IL-6, IFNγ, and TNF α are also associated with AD. Ang-I and Ang-II are also found to mediate the progression of AD. Complement factors B, C4b and H are differentially expressed in AD. Overall, a number of adipocyte derived cytokines are found to be dysregulated in AD whose role in the disease remains to be studied. We, in this review, comprehend the current findings relating adipose derived factors in AD with special emphasize on autophagy.